Cytokine Gene Polymorphisms in Acute Pancreatitis - Sargen, Kevin; Demaine, Andrew G; Kingsnorth, Andrew N (JOP. Journal of the Pancreas, 2016)
Context Pro-inflammatory and regulatory cytokines play a key role in the pathogenesis of acute pancreatitis. Genetic loci encoding cytokines have been shown to be polymorphic, in some cases influencing protein expression. Objective To investigate if TNF and IL-10 gene loci are associated with the occurrence or severity of acute pancreatitis. Setting Acute surgical unit within large district hospital serving a population of 500,000. Methods Three TNF microsatellite loci (TNFa, TNFb, TNFc), the TNF-308 polymorphism, the IL-10.G microsatellite locus, and 3 bi-allelic polymorphisms in the IL-10 5’ region were typed using PCR in 135 acute pancreatitis patients and ethnically matched normal controls (n=107). Aetiology of disease was determined and patients grouped according to disease severity by assigning an organ failure score or classification according to the Atlanta system. Main outcome measures Allelic frequency of polymorphic loci in patients with different aetiology and disease course in acute pancreatitis. Results No difference was noted in allelic frequency of any of the cytokine gene loci between groups stratified according to disease severity. When aetiology was studied again there was no significant difference in allelic frequency. Conclusions The cytokine gene polymorphisms studied play no part in determination of disease severity or susceptibility to acute pancreatitis. Image: Structural formula of Tumor necrosis factor-alpha (TNF-alpha) (Author: Doxepine; Wikimedia Commons)